2016
DOI: 10.1021/acs.macromol.6b01297
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength Tuning of the Photonic Band Gap of an Achiral Nematic Liquid Crystal Filled into a Chiral Polymer Scaffold

Abstract: We demonstrate electric-field-induced wavelength tuning of the entire photonic band gap of an achiral nematic liquid crystal (LC) filled into a chiral polymer scaffold. This chiral polymer scaffold has been formed by creating a template of a chiral nematic LC phase, which remarkably does not compromise the optical finesse of the band gap when compared to that of a conventional, polymer-stabilized chiral nematic LC. We present results on the spectral shift and temporal evolution of the photonic band gap in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Tailoring polymer architectures with innovations is regarded as a superior procedure for a wide array of applications. In general, the tailoring of SCLCPs can be categorized into three parts including the polymeric matrix, LC moiety and flexible spacer. Recently, there have been contributions to the rational design of polymer matrixes to determine precise structure–property relationships in LC functional materials. Polymeric matrixes are divided into many categories according to their composition, including homopolymers, copolymers and complexes and others. The use of copolymers instead of homopolymers as polymeric matrixes could facilitate major specific advantages.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Tailoring polymer architectures with innovations is regarded as a superior procedure for a wide array of applications. In general, the tailoring of SCLCPs can be categorized into three parts including the polymeric matrix, LC moiety and flexible spacer. Recently, there have been contributions to the rational design of polymer matrixes to determine precise structure–property relationships in LC functional materials. Polymeric matrixes are divided into many categories according to their composition, including homopolymers, copolymers and complexes and others. The use of copolymers instead of homopolymers as polymeric matrixes could facilitate major specific advantages.…”
Section: Results and Discussionmentioning
confidence: 99%
“…To mimic their performance in reflectivity, several stacked structures were made before Guo et al However, such stacked layers had drawbacks such as the diffusion between soft layers in fluid media, optical defects and losses at the interfaces. Wood et al [74], refilled the polymer template made from a chiral nematic liquid crystal with an achiral nematic liquid crystal. They tuned the photonic band gap in the refilled system by applying an electric field.…”
Section: Chiral Nematic and Blue Phasesmentioning
confidence: 99%
“…In this study, it was found that a negative strain introduced on the polymeric film produced an increase in the sensitivity of the sensor up to 15 times compared to their unstrained counterparts. Wood et al [74], refilled the polymer template made from a chiral nematic liquid crystal with an achiral nematic liquid crystal. They tuned the photonic band gap in the refilled system by applying an electric field.…”
Section: Chiral Nematic and Blue Phasesmentioning
confidence: 99%
“…Past decades are characterized by the explosive development of technologies based on optoelectronics and photonics . The modern elemental base of these technologies includes refractive, diffraction and optical fiber components.…”
Section: Introductionmentioning
confidence: 99%